Analisis Pengaruh Harga Dan Promosi Terhadap Keputusan Konsumen Dalam Pembelian Produk Online Di Bukalapak - roswaty, roswaty (Jurnal Keuangan dan Bisnis, 2022)
The objective of this research was to determine the influence of prices and promotions on online goods purchasing decisions at Bukalapak with purchases concentration on fashion products. The tests were administered to 60 people taken by using non probability sampling techniques, while the determination of respondents was taken through a saturated sampling method. The technical analysis calculation was done by using the t test method, correlation test, determination test and multiple linear regression test. The results of the t test showed that t count of X1 (price) was 2.498 at the level of sig 0.015 and t count of X2 (promotion) was 2.043 at the level of sig 0.048. The results of the correlation test indicated that Y and X1 were 0.386, Y and X2 were 0.318. The result of the determination test was 0.682. The results of the multiple linear regression tests were Y = 2.264 + 0.263 + 0.218. The results of this research revealed that prices and promotions had a positive influence on goods purchasing decisions. The most influential factor in purchasing decisions online at Bukalapak was Promotion. Price factor remains a significant contributor for the presentation of purchasing decision, because in Bukalapak can be made of bargaining system. Assessment of satisfaction in the Bukalapak application on 19 March 2020 at 11am on Playstore show a rating 4,5 of 5,0 with a total rating of 922.968 people. Bukalapak must maintain the price level by working with MSMEs and making several new promotions. Key word : Price, Promotion, Consumer Decision